Flight take-off and walking behavior of insecticide-susceptible and – resistant strains of Sitophilus zeamais exposed to deltamethrin - Guedes, N. M. P.; Guedes, R. N. C.; Ferreira, G. H.; Silva, L. B. (Bulletin of Entomological Research, 2009)
Insects have evolved a variety of physiological and behavioral responses to various toxins in natural and managed ecosystems. However, insect behavior is seldom considered in insecticide studies although insects are capable of changing their behavior in response to their sensory perception of insecticides, which may compromise insecticide efficacy. This is particularly serious for insect pests that are physiologically resistant to insecticides since insecticide avoidance may further compromise their management. Locomotion plays a major role determining insecticide exposure and was, therefore, considered in investigating the behavioral responses of male and female adult insects from an insecticide-susceptible and two insecticide-resistant strains of the maize weevil Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae), a major pest of stored cereals. Different dose- dependent behavioral responses were expected among strains with behavioral resistance less likely to occur in physiologically resistant insects since they are able to withstand higher doses of insecticide. The behavioral responses to deltamethrin- sprayed surfaces differed among the maize weevil strains. Such responses were concentration-independent for all of the strains. Stimulus-independent behavioral resistance was unrelated to physiological resistance with one resistant strain exhibiting higher rates of flight take-off and the other resistant strain exhibiting lower flight take-off. Female mobility was similar for all strains, unlike male mobility. Males of each strain exhibited a pattern of mobility following the same trend of flight take-off. Behavioral patterns of response to insecticide are, therefore, variable among strains, particularly among insecticide-resistant strains, and worth considering in resistance surveys and management programs.
Keywords: Behavioral resistance; Insecticide avoidance; Insecticide resistance; Maize weevil; Repellence; Mobility; Pyrethroid; Stored grains